Drop by drop - Llywelyn, Morgan (Llywelyn, Morgan. Step by step, 2018)
In this first book in the Step By Step trilogy, global catastrophe occurs as all plastic mysteriously liquefies. All the small components making many technologies possible<U+2015>navigation systems, communications, medical equipment<U+2015>fail. In Sycamore River, citizens find their lives disrupted as everything they've depended on melts around them, with sometimes fatal results. All they can rely upon is themselves. And this is only the beginning . . .